Reform of Human Trafficking Victim Protection Policy in Indonesia: A Human Rights and Restorative Justice Perspective - Fero Sanjaya; Herlita Eryke (UNIVERSITAS PAKUAN, 2026)
Purpose of this paper is to examine the legal framework of victim protection in human trafficking cases in Indonesia, which currently faces significant challenges regarding the fulfillment of victims' rights to restitution. Despite the existence of Law No. 21 of 2007, victims often encounter systemic barriers in obtaining recovery, leading to secondary victimization. Methods used in this study follow a normative legal research approach with statutory, conceptual, and case perspectives, specifically analyzing Supreme Court Decision No. 2355 K/Pid.Sus/2022. Research results indicate that the current restitution mechanism is merely decorative and highly dependent on the perpetrator's financial capacity, which is often non existent or hidden. The study finds a significant legal gap where the state lacks a mandatory safety net for victims when perpetrators fail to pay. Analysis reveals that the protection policy is still heavily